Devices for optoelectronics - Leigh, Wallace B. (Optical engineering (Marcel Dekker, Inc.), 1996)
This well-balanced reference/text offers thorough coverage of optical devices utilized in communication and information processing systems - highlighting the physics of optoelectronics necessary for both hybrid and monolithic optical integrated circuits (OICs) and bridging the information gap between thin-film switches and active semiconductors by analyzing lithium niobate as well as compound semiconductor devices. Discussing optical transmitters, receivers, and switches, Devices for Optoelectronics provides an introduction to material-photon interactions that facilitates an understanding of device development...explains laser and light-emitting diode devices...examines charge-coupled devices and array detectors...describes nonlinear devices for optical integrated circuits...addresses numerous practical applications...and much more.